Studi Partisipasi Politik Perempuan Kabupaten Gorontalo - Sahi, Nirmala Afrianti (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The widely opening of the democratic system in Indonesia provides a good opportunity for the development of the nation's politics. One of the indicators is the running of a democratic political system and measuring the level of public participation is the involvement of citizen participating in elections. The purpose of this study was to determine the political participation of women in the District of Gorontalo and the obstacles faced by women politicians in Gorontalo District at the period of 2009-2014. The methodology used was a descriptive qualitative analysis. Primary data were collected through structured interviews and observation. The secondary data obtained from research reports, journals, and the data available in each political party, the KPU, and the institution associated with the election. The sample consisted of 10 informants of women politicians, election commission, NGOs, head women's empowerment, academicians, and leaders of the party. The result showed that women's political participation is still low in Gorontalo District. It is suggested women politicians should enhance their capacity building, networking with women's organizations and NGOs as well as the need for the party's commitment to give priority to women.Keyword: Women’s Political Participation